Mini percutaneous nephrolithotomy treat the large upper ureteric stone - Haidar Hazim Mohammed Al Jabban; Raed Hmood Afiet; Ihab Saad Khewkah (Romanian Journal of Medical Practice, 2024)
Background. The incidence of kidney stones has been raised all over the world. Nephrolithiasis is the most common cause of illnesses in western countries and has been rising in its incidence in developing countries. PCNL describe the management of large renal calculi when measuring >20 mm and even for smaller ones of lower pole with excellent stone-free rate reach to 98%. Aim. To evaluate the mini-percutaneous nephrolithotomy (mini-PCNL) safety used to cure upper ureteral and renal stones with assessing the complication and procedure outcome in Iraqi patients. Method. This is a prospective study done between October 2022 and September 2023 in Ghazi Al-Hariri for Surgical Specialties Hospital, Medical city, with 100 patients enrolled who underwent mini-PCNL. All patients had upper ureteral and renal stones (size ≥20 mm). The nephroscope tube was utilized. The stones were destroyed by pneumatic lithotripter. Complications and outcomes were determined immediately postoperative via X-ray of the ureters, kidneys and bladder. Ultra-sonography also used to determine safety and efficacy of procedure. Results. The cases mean age was 55.8 ± 12.3 years, and their BMI was 29.5 ± 5.9 kg/m2. The size of mean stone was 22.5 ± 17.9 mm. The stone-free rate (SFR) was 94.7%. The post-operative hospital stay mean was 3.6 ± 2.7 days. The Hb drop mean was 0.6 ± 0.3 g/dL. There were none of our cases had organ trauma or any complications. Thirty cases required additional subsequent extra-corporeal shock wave lithotripsy. Conclusion. The mini-PCNL is effective and safe in cases of upper ureteral and renal stones ≥20 mm. Researches with a larger multi-center cohorts may be needed to validate these techniques.